Strategisk kompetensförsörjning i offentlig sektor - Leinonen, Rebecka (2014)
This is a study of how Luleå municipality relates to human resource planning. The purpose with this study was to describe and analyze how the municipality works with human resource planning and analyze the development opportunities in order to provide suggestions for improvements. To answer the purpose, four questions was formulated; what strategies for human resource planning was Luleå Municipality using? How do they prepare themselves for their upcoming challenges? What do human resource planning mean for the managers? Which resources are available concerning human resource planning?The data collection was primarily done through nine interviews but was supplemented with documents established by the municipality. The study shows that the municipality had human resource planning strategies, with the exception of strategies regarding skill transfers and follow-up after a skill development. The study also shows that the municipality had the methods and tools that were needed to succeed with an efficient human resource planning. The only thing that were missing was the manager’s time and abilities to think in a long-term perspective. The human resource planning had been made a part of the financial management process which opens up new opportunities for the municipality to develop their work with human resource planning. Validerat; 20140614 (global_studentproject_submitter)